CINCA/NOMID is a rare autoinflammatory syndrome in rheumatological practice. Experience of diagnosis, management and therapy with interleukin-1 inhibitors - S. O. Salugina; E. S. Fedoro; A. V. Torgashina (Современная ревматология, 2024)
Objective: to present the experience of diagnosis, management and therapy with interleukin-1 inhibitors (iIL1) in patients with Chronic Infantile Onset Neurologic Cutaneous Articular/Neonatal Onset Multisystem Inflammatory Disease (CINCA/NOMID) according to the Russian Federal Rheumatological Center data.Material and methods. From 2007 to 2023, eight patients were included in the study (7 men) aged 10 months to 33 years, including 3 with a disease duration of more than 10 years (13, 17 and 33 years). Genetic testing was performed in all patients and mutations in the NLRP3 gene were identified in 6 cases.Results and discussion. The age of onset of the disease ranged from 0 to 6 months. The delay in diagnosis and prescription of therapy ranged from 10 months to 33 years. All patients had the classic manifestations of CINCA/NOMID, including fever, rash, central nervous system (CNS) involvement, elevated ESR and CRP levels, 6 patients had articular manifestations, 7 had ocular manifestations and 6 had sensorineural hearing loss. Amyloidosis was detected in 1 case. All patients were prescribed iIL1. Anakinra was used in 6 patients (in 5 as the first line, in 1 as the second line therapy) with a positive response; subsequently 2 of these patients were switched to canakinumab once every 4 weeks (1 patient deteriorated and was readministered anakinra). Five patients received canakinumab (3 as first-line therapy, 2 as second-line therapy), 1 patient was switched to anakinra due to insufficient CNS response. The response to iIL1 therapy was positive in all patients, but incomplete in some of them due to the severity of the manifestations and the presence of irreversible organ damage.Conclusion. Patients with CINCA/NOMID have a severe disease and a poor prognosis. In this context, early administration of iIL1 is necessary. In the case of CNS involvement, the use of anakinra is preferable, as it is characterized by better penetration of the blood-brain barrier and is therefore more effective. Later it is possible to switch the patient to canakinumab, however, to achieve a complete response, it is sometimes necessary to increase the dose of the drug and reduce the interval between doses.